Case Report: Osmotic Demyelination Syndrome After Transcatheter Aortic Valve Replacement: Case Report and Review of Current Literature - Jin, Xinhao; Wang, Yonggang (Frontiers in Medicine, 2022)
Background Osmotic demyelination syndrome (ODS) has a low incidence but is a life-threatening neurological disorder whose common cause is rapid overcorrection of chronic hyponatremia. Transcatheter aortic valve replacement (TAVR) is a new and important therapy for patients with aortic valve stenosis. In this article, we discuss the case of a 64-year-old woman who developed ODS after TAVR and provide a literature review. Case Presentation A 64-year-old female patient was admitted to the hospital with chest tightness, shortness of breath, and fatigue for 2 months, with worsening of symptoms for 3 days prior to presentation. Auscultation revealed crackles in the lung fields, and systolic murmurs could be easily heard in the aortic area. Echocardiography showed severe aortic stenosis. Chest X-ray showed pulmonary oedema. Laboratory examinations showed that her serum sodium was 135 mmol/L. The patient received a diuretic to relieve her symptoms but showed little benefit. Her symptoms worsened, and her blood pressure dropped. Then, she underwent emergency TAVR under extracorporeal membrane oxygenation (ECMO) support. After the operation, her urine output increased markedly, and serum sodium increased sharply from 140 to 172 mmol/L. An MRI scan showed multiple lesions in the pons suggestive of ODS. Conclusion To date, this is the first reported case of a patient who developed ODS after receiving TAVR. In current clinical practice, diuretics are often used in aortic stenosis patients because of pulmonary oedema. After a patient receives TAVR, kidney perfusion pressure quickly returns to normal, and with the residual effect of a high-dose diuretic, balances of fluid volume and electrolyte levels in this phase are quite fragile and must be carefully managed. If a patient has neurological symptoms/signs during this phase, ODS should be considered, and MRI might be necessary.